Primary adenoid cystic carcinoma of the bronchus in a female teenager. (29th November 2010) - Masih, I; Porter, G; Porter, S; Clarke, R; Sidhu, P; Harney, J; McCarthy, A; Convery, R
Abstract : Primary adenoid cystic carcinoma (ACC) of the lung is an extremely rare malignant lung neoplasm. ACC of salivary glands of the head and neck, lachrymal glands, breast, skin, vulva and trachea have been frequently reported disease patterns in the literature, but it is unique to see this rare lung tumour in a patient as young as 14 years old. No double blind placebo, multicentre treatment data are available. Surgery is considered as the cornerstone of the treatment. Prognosis is variable and adjuvant radiotherapy has been found beneficial for prolonged survival. Our report of primary lung ACC in a young girl is a complex case due to young age, a different way of presentation and staging on diagnosis. It has been a quite challenging clinical scenario for the multidisciplinary lung cancer treating team involved in the clinical care. Prognosis remains unpredictable and uncertain despite the best present day evidence-based treatment.